Future of fish for food and nutrition security in Nigeria - Chan, Chin Yee; Long Chu, Hoang; Tran, Nhuong; Sari, Evren Can; Cheong, Kai Ching; Olagunju, Olanrewaju; Shikuku, Kelvin; Byrd, Kendra; Diyzee, Kanar; Subasinghe, Rohana; Siriwardena, Sunil (WorldFish, 2024)
The objective of this study was to provide a future macro picture of the fish sector in Nigeria until 2050 by projecting the dynamics of fish supply and demand and drawing policy implications on food security that can be of interest to policymakers in Nigeria. The study uses a multispecies–multisector–multiregion equilibrium model to provide projections for Nigeria’s fish sector and its impact on food and nutrition security by mid-century. The model incorporates both quantitative and qualitative insights from 63 stakeholders with various expertise in Nigeria to verify data, validate preliminary projection results and explore six alternative scenarios. Under the business-as-usual (BAU) scenario, the demand for fish in Nigeria would increase relatively fast, fueled by economic and demographic growth. The country’s current domestic fish production will not adequately meet the rapidly growing demand, leading to increased reliance on imports, and imports would increase until 2050 in all alternative scenarios. Aquaculture is likely to become the dominant source of fish production, accounting for over 60% of total fish supply by 2050.